Enhancing academic librarians’ soft skills to face artificial intelligence changes using the ADKAR model - Resty Jayanti Fakhlina; Lolytasari Lolytasari; Febriyanti Bifakhlina; Muhamad Riza (Berkala Ilmu Perpustakaan dan Informasi, 2026)
Introduction. This study analyses the development of soft skills among librarians at the Indonesian State Islamic University (PTKIN) in the context of AI-based technological transformation, using the ADKAR model as an analytical framework. Research Methods. A descriptive quantitative survey targeted 83 librarians from a pool of 470 PTKIN librarians, using a Likert-scale questionnaire across five ADKAR dimensions: awareness, desire, knowledge, ability, and reinforcement. Data Analysis. Descriptive statistics (frequencies, percentages, and mean scores) identified dominant dimensions and readiness gaps by education, tenure, and position. Results. Awareness, desire, and ability were dominant (>70% positive responses) among Bachelor’s/Master’s degree holders and 11-20 year veterans. Knowledge and reinforcement showed gaps (<6% contribution) for Diploma staff and support roles, indicating an imbalance in AI adoption and weak institutional support. Conclusion: The paper recommends that the targeted professional programs are necessary to boost AI literacy, digital adaptability, and collaboration, guiding PTKIN libraries in tiered training, mentoring, and policies for sustainable AI integration.